Association between Genetic Variation in the Oxytocin Receptor Gene and Emotional Withdrawal, but not between Oxytocin Pathway Genes and Diagnosis in Psychotic Disorders - Haram, Marit; Tesli, Martin; Bettella, Francesco; Djurovic, Srdjan; Andreassen, Ole Andreas; Melle, Ingrid (Frontiers in Human Neuroscience, 2015)
Social dysfunction is common in patients with psychotic disorders. Oxytocin is a neuropeptide with a central role in social behaviour. This study aims to explore the relationship between oxytocin pathway genes and symptoms related to social dysfunction in patients with psychotic disorders. We performed association analyses between four oxytocin pathway genes (OXT, OXTR, AVP, CD38) and four areas of social behaviour-related psychopathology as measured by Positive and Negative Syndrome Scale (PANSS). For this purpose, we used both a polygenic risk score (PGRS) and single OXTR candidate SNPs previously reported in the literature (rs53576, rs237902, rs2254298). A total of 734 subjects with DSM-IV psychotic spectrum disorders and 420 healthy controls were included. Oxytocin pathway PGRSs were calculated based on the independent Psychiatric Genomics Consortium study sample. There was a significant association between symptom of Emotional Withdrawal and the previously reported OXTR risk allele A in rs53576. No significant associations between oxytocin pathway gene variants and a diagnosis of psychotic disorder were found. Our findings indicate that while oxytocin pathway genes do not appear to contribute to the susceptibility to psychotic disorders, variations in the OXTR gene might play a role in the development of impaired social behaviour.